Microservices-Based System Design for Ensuring High Availability and System Reliability - Khalid Khan; Zulfiqur Rahman; Amrita Khan; Anamika Roy; Jhon Kabir (Eastasouth Institute, 2024)
The increasing demand for highly available and reliable software systems has driven the adoption of microservices-based architectures in modern distributed environments. The analysis is supported by two figures that illustrate key performance metrics such as system availability, mean time to repair (MTTR), mean time to failure (MTTF), response time, throughput, and failure rate under dynamic workloads. The results indicate that monolithic systems exhibit lower availability, higher response time, and increased failure rates, making them less suitable for modern, dynamic environments. The transition to microservices architecture improves fault isolation and scalability, resulting in enhanced reliability and reduced downtime. Further improvements are observed with the integration of load balancing mechanisms, which distribute workload efficiently across service instances, thereby increasing system resilience. The highest performance is achieved when microservices are combined with orchestration platforms such as Kubernetes. This configuration demonstrates near-optimal availability, minimal recovery time, and superior scalability, as evidenced by reduced response times and increased throughput. The study highlights the critical role of architectural design and supporting technologies in achieving high availability and reliability. The findings provide valuable insights for system designers and organizations aiming to build robust and scalable applications. Overall, microservices-based system design, when combined with advanced deployment and management strategies, offers a powerful solution for addressing the challenges of modern distributed systems.